Performance of Public Health Extension Officers in Health Promotion Practices at District Health Services - Kamaruddin, Muh. Ihsan; Nawangwulan, Kurniati; Yusfik, Yusnita; Nursinah, Andi; Mainassy, Meillisa Carlen; Restiyanti, Yuli (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The criteria for determining mandatory authority in the health sector are that it is a service, high priority because it protects people's rights, protects national interests, is a national commitment and is the main cause of death and morbidity, is measurable and carried out continuously and the minimum service standards set by the health service have not been achieved. district, because the performance of public health officers is still lacking in providing education to the community. The aim of this research is to analyze the factors that influence the performance of public health workers in health promotion practices at the District Health Service. This research uses an explanatory study method with a cross sectional approach. Data collection was carried out by means of interviews and observations with a sample size of 87 officers. The results of the research show that the performance of public health extension officers in health promotion practices at the Sidrap District Health Service is poor, namely 56.3% and only 43.7% have good performance. The variable that is directly related to the performance of public health extension officers is level of education, training, knowledge, skills and leadership. The variable that most influences the performance of public health extension officers is education level.